Efficiency Evaluation of Credit Guarantee Corporation (Malaysia) Berhad, 1974-1999 - Ong, Hway Boon (2001)
This study is conducted to evaluate the efficiency of CGC in providing guarantee coverage and direct lending to SMEs. The efficiency evaluation of CGC is conducted in three stages. First, it is conducted for single output where technical and scale efficiency evaluation are carried out for guarantees issued for each type of loans categorised under general business, manufacturing and agriculture sectors. Second, two outputs efficiency evaluation is executed for guaranteed issued for loans categorised under general business and manufacturing sectors, general business and agriculture sectors, as well as manufacturing and agriculture sectors. Lastly, efficiency evaluation of three outputs, namely guarantees issued for loan categorised under all three general business, manufacturing and agriculture sectors is conducted.Despite the fact that CGC was operating at a relatively low level of overall technical efficiency, the results suggested that CGC is most efficient in granting credit guarantees to three sectors of the economy than one and two sectors. By providing credit guarantees to the three sectors, namely general business, manufacturing and agriculture sectors, the average overall technical efficiency score was higher as compared to single and two outputs. Though the result suggested that both pure technical and scale inefficiency contributed to the inefficiency of CGC, pure technical inefficiency contributed slightly more than scale inefficiency. As such, CGC should seriously consider reallocating its existing inputs as well as to increase the amount of credit guarantees granted to general business, manufacturing and agriculture sectors in order to achieve a reasonable level of efficiency.